Structural and Functional Characterization of a Nav1.5-Mitochondrial Couplon. Issue 3 (21st December 2020) - Pérez-Hernández, Marta; Leo-Macias, Alejandra; Keegan, Sarah; Jouni, Mariam; Kim, Joon-Chul; Agullo-Pascual, Esperanza; Vermij, Sarah; Zhang, Mingliang; Liang, Feng-Xia; Burridge, Paul; Fenyo, David; Rothenberg, Eli; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: The cardiac sodium channel NaV 1.5 has a fundamental role in excitability and conduction. Previous studies have shown that sodium channels cluster together in specific cellular subdomains. Their association with intracellular organelles in defined regions of the myocytes, and the functional consequences of that association, remain to be defined. Objective: To characterize a subcellular domain formed by sodium channel clusters in the crest region of the myocytes and the subjacent subsarcolemmal mitochondria. Methods and Results: Through a combination of imaging approaches including super-resolution microscopy and electron microscopy we identified, in adult cardiac myocytes, a NaV 1.5 subpopulation in close proximity to subjacent subsarcolemmal mitochondria; we further found that subjacent subsarcolemmal mitochondria preferentially host the mitochondrial NCLX (Na + /Ca 2+ exchanger). This anatomic proximity led us to investigate functional changes in mitochondria resulting from sodium channel activity. Upon TTX (tetrodotoxin) exposure, mitochondria near NaV 1.5 channels accumulated more Ca 2+ and showed increased reactive oxygen species production when compared with interfibrillar mitochondria. Finally, crosstalk between NaV 1.5 channels and mitochondria was analyzed at a transcriptional level. We found that SCN5A (encoding NaV 1.5) and SLC8B1 (which encode NaV 1.5 and NCLX, respectively) are negatively correlated both in a human transcriptome data set (Genotype-Tissue Expression) and in human-induced pluripotent stem cell-derived cardiac myocytes deficient in SCN5A . Conclusions: We describe an anatomic hub (a couplon) formed by sodium channel clusters and subjacent subsarcolemmal mitochondria. Preferential localization of NCLX to this domain allows for functional coupling where the extrusion of Ca 2+ from the mitochondria is powered, at least in part, by the entry of sodium through NaV 1.5 channels. These results provide a novel entry-point into a mechanistic understanding of the intersection between electrical and structural functions of the heart.